Prediction of material removal rate in chemical mechanical polishing via residual convolutional neural network. (February 2021) - Zhang, Jiusi; Jiang, Yuchen; Luo, Hao; Yin, Shen
Abstract: Chemical mechanical polishing (CMP) is one of the most powerful technologies to achieve global planarization for precision machining of the wafer surface. CMP contributes to intelligent manufacturing in Industry 4.0. Prediction of the material removal rate (MRR) is of vital significance for product quality control during the CMP process. There is no generally accepted theory to expound the principle of material removal in CMP. This paper proposes data-driven approaches to predict MRR based on deep learning methods to pursue better prediction performance. Random forest is employed to obtain the process variables which have a significant influence on MRR prediction and act as the input of the neural network. In addition, it is firstly proposed to predict MRR with the aid of residual convolutional neural network (ResCNN). The dataset provided by the PHM2016 Data Challenge is applied to compare the MRR prediction performance of the ResCNN with the CNN-based approach. Experimental results show that the prediction performance of ResCNN outperforms all the existing approaches reported in the literature.